2014
DOI: 10.1152/ajpheart.00920.2013
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase-dependent regulation of myogenic response and blood pressure

Abstract: Sun D, Cuevas AJ, Gotlinger K, Hwang SH, Hammock BD, Schwartzman ML, Huang A. Soluble epoxide hydrolase-dependent regulation of myogenic response and blood pressure. Am J Physiol Heart Circ Physiol 306: H1146-H1153, 2014. First published February 21, 2014 doi:10.1152/ajpheart.00920.2013 are metabolites of arachidonic acid via cytochrome P450 (CYP)/epoxygenases. EETs possess cardioprotective properties and are catalyzed by soluble epoxide hydrolase (sEH) to dihydroxyeicosatrienoic acids (DHETs) that lack vasoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 57 publications
(70 reference statements)
4
35
1
Order By: Relevance
“…The recognition that the female sex and/or estrogen favors the contribution of EETs has been documented (38). We also demonstrated that, in resistance arteries, actions of EETs become discernable when EET degradation is compromised (40). Thus, via genetic disruption of the sEH gene to increase intracellular EET levels and prolong their vascular actions, we were able to evaluate the pathophysiological significance of sEH/EETs in the regulation of pulmonary and systemic circulations, as a function of sex.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The recognition that the female sex and/or estrogen favors the contribution of EETs has been documented (38). We also demonstrated that, in resistance arteries, actions of EETs become discernable when EET degradation is compromised (40). Thus, via genetic disruption of the sEH gene to increase intracellular EET levels and prolong their vascular actions, we were able to evaluate the pathophysiological significance of sEH/EETs in the regulation of pulmonary and systemic circulations, as a function of sex.…”
Section: Discussionmentioning
confidence: 63%
“…As described previously (40), cryorecovered heterozygous (Ephx2 ϩ/Ϫ , B6.129X-Ephx2tm1Gonz/J) and WT (Ephx2 ϩ/ϩ ) mice were received from the Jackson Laboratory (Bar Harbor, ME) and the homozygous (Ephx2 Ϫ/Ϫ ) mice were bred in the Department of Comparative Medicine, New York Medical College.…”
Section: Twelve-to 15-wk-old Male (M) and Female (F) Ephx2mentioning
confidence: 99%
See 1 more Smart Citation
“…16 These observations likely reflect EET attenuation of vascular myogenic responses in resistance arterioles, as shown in sEH knockout mice or with sEH inhibitors. 17 The correlation between DHET and plasma aldosterone in SR could reflect parallel dichotomization of both parameters by changes in salt balance (inhibition by salt loading and stimulation by salt depletion). However, it was also present during the periods of small variance of aldosterone levels (baseline and high-salt days).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of endothelial removal and the intact vasomotor function of smooth muscle were validated by the loss of arteriolar dilation to the endothelium‐dependent vasodilator acetylcholine (10 −6  mol/L) and maintained dilation to the nitric oxide (NO) donor (NONOate, 10 −6  mol/L), respectively (Table). 9 …”
Section: Resultsmentioning
confidence: 99%